Exosomal miRNAs as Novel Pharmacodynamic Biomarkers for Cancer Chemopreventive Agent Early Stage Treatments in Chemically Induced Mouse Model of Lung Squamous Cell Carcinoma - Zhou, Yu (Cancers (Basel), 2019)
Background: Chemopreventive agent (CPA) treatment is one of the main preventive options for lung cancer. However, few studies have been done on pharmacodynamic biomarkers of known CPAs for lung cancer. Materials and methods: In this study, we treated mouse models of lung squamous cell carcinoma with three different CPAs (MEK inhibitor: AZD6244, PI-3K inhibitor: XL-147 and glucocorticoid: Budesonide) and examined circulating exosomal miRNAs in the plasma of each mouse before and after treatment. Results: Compared to baselines, we found differentially expressed exosomal miRNAs after AZD6244 treatment (n = 8, FDR < 0.05; n = 55, raw p-values < 0.05), after XL-147 treatment (n = 4, FDR < 0.05; n = 26, raw p-values < 0.05) and after Budesonide treatment (n = 1, FDR < 0.05; n = 36, raw p-values < 0.05). In co-expression analysis, we found that modules of exosomal miRNAs reacted to CPA treatments differently. By variable selection, we identified 11, 9 and nine exosomal miRNAs as predictors for AZD6244, XL-147 and Budesonide treatment, respectively. Integrating all the results, we highlighted 4 miRNAs (mmu-miR-215-5p, mmu-miR-204-5p, mmu-miR-708-3p and mmu-miR-1298-5p) as the key for AZD6244 treatment, mmu-miR-23a-3p as key for XL-147 treatment, and mmu-miR-125a-5p and mmu-miR-16-5p as key for Budesonide treatment. Conclusions: This is the first study to use circulating exosomal miRNAs as pharmacodynamic biomarkers for CPA treatment in lung cancer.